Corporate Resultative Innovativeness Assessment on the Example of Polish IT Companies - Tomasz L. NAWROCKI (Communications of International Proceedings, 2020)
The paper aims to present an empirical application of an originally developed solution for corporate resultative innovativeness assessment and comparison. The proposed solution provides a framework for resultative innovativeness assessment of enterprises based on the methodology used in multivariate comparative analysis. Within the proposed method of assessing corporate resultative innovativeness, the focus is on its general qualitative dimension as defined in the Oslo manual and it is assumed that the individual assessment criteria are based on generally available data published by enterprises in their periodic reports (mainly annual, due to greater completeness of data and verification by external auditors). In this context, selected companies from the information technology sector listed on the Warsaw Stock Exchange were examined. The need for corporate innovativeness measurement and evaluation for management purposes arises from its growing importance in building enterprise value and achieving long-term competitive advantage. The proposed solution enables a fairly current and good orientation in the area of the results of innovation activity carried out by the assessed enterprises. This can be the basis for various comparison analysis and managerial decisions regarding e.g. innovation management as well as managing corporate image and reputation.
Keywords: Corporate Innovativeness; Results of Innovation Activity; Innovativeness Assessment; Multivariate Comparative Analysis.